Preparation and Characterization of Epoxy Acrylate/ Mesoporous Silica Composite Materials - Yang, Zehui; Ni, Aiqing; Wang, Jihui; Yin, Yanzi (Asian Journal of Chemistry, 2012)
Mesoporous silica was prepared by sol-gel method. TEOS was the resource of inorganic materials and EO20PO20EO20 (P123) as template. The structure of mesoporous silica was tested by SEM and TEM. The diameter of mesoporous silica was 500 nm and the length was about 1μm. The diameter of pore path was approximate 5 nm. The BET area was 492 m2g-1 and the pore volume was 1.009 cm3g-1 via the experiment of nitrogen adsorption-desorption. Mesoporous silica was uniformly dispersed in epoxy acrylate resin. EA/mesoporous silica begun evident weight loss at 325 ºC, 25 ºC higher than pure epoxy acrylate resin.